Dynamics of Extreme Drought and Extreme Wet in Indonesia: Analysis of Frequency, Trends, and Spatial Distribution 1995–2024 - Suhadi, Suhadi; Khairunnisa Putri, Jamiatul; Putra Sairi, Andi; Hayati, Tazkia; Anjli, Neneng; Diansyah, Pras; Mabruroh, Faizatul (Jurusan Fisika FMIPA Universitas Andalas, 2026)
The climatological pattern of rainfall and the occurrence of extreme drought and extreme wet in Indonesia are influenced by monsoon dynamics, topography, and Sea Surface Temperature Anomalies (SSTA) in the Pacific and Indian Oceans. Although studies on extreme droughts in Indonesia exist, none have quantified the spatial frequency of extreme drought and rainfall events. This study aims to determine the frequency and trend of extreme drought and extreme rain in Indonesia during 1995–2024. Gridded precipitation data from the Global Precipitation Climatology Center (GPCC) with 0.5° resolution were used. Frequencies of extreme drought and extreme wet were calculated using the Standardized Precipitation Index (SPI), while trends were estimated from the Poisson Regression slope. Frequency and trend were computed for the grid to represent spatial distributions. SPI results at 3, 6, and 12-month scales show Sumatra, Kalimantan, and Papua experienced extreme droughts 8–12 times, with varying frequencies. Extreme droughts were widespread in eastern Indonesia during the dry season (JJA and SON), with longer persistence in SPI-6 and SPI-12. In contrast, extreme wet events occurred more frequently in western and central Indonesia, during the rainy season (DJF), when the western monsoon transported moisture from the Indian Ocean.